A snapshot of the Portuguese e-banking activity: Insights and a conceptual framework to allocate strategic hindrances - Ferreira, F.; Barata, J. M. M. (International Journal of Electronic Business, 2011)
It is widely known that the emergence of Information and Communication Technologies (ICTs) presents a challenge to financial institutions in terms of providing alternative means of services. However, this progression has its own shortcomings. This paper aims to offer a snapshot of the electronic banking activity in Portugal by highlighting some of the major strategic hindrances faced by the sector's evolution. Our study also aims to provide a conceptual framework where barriers to the e-banking evolution are allocated into four major categories of strategic hindrances. To determine the practical relevance of our framework, a panel study has been conducted, and the framework's strengths and weaknesses have also been discussed.